Influence of public-private partnership mechanisms on health investments in health care - A. V. Ivanyuk (Kazimierz Wielki University, 2020)
The objective. To consider the mechanisms of public-private partnership (PPP) as a way to attract investment into the health care system and find out the existence in Ukraine of  a legal basis for the implementation of PPP in health care sector. Materials and methods. The mechanisms and possibilities of PPP projects realization in health care sector have been studied with the use of systematic approach, systematic analysis and information-analytical method. Results. Based on the analysis of international experience, the article presents the key models of PPP used in health care. The legal and institutional bases for the implementation of the PPP investment mechanism in the health care system of Ukraine are determined. The benefits of implementing PPP projects in health care for the state, private partners and the general population are shown. The basic principles of PPP and key directions of introduction of mechanisms of public-private partnership in the field of health care are substantiated. The existing problems for the formation of these mechanisms in the health care of Ukraine are revealed. Conclusions. Public-private partnership is a promising direction of investment attraction in the health care system. There is a necessary legal framework for the implementation of PPP projects in health care inUkraine. .